2015
DOI: 10.1371/journal.pone.0120051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dual Treatment with SDF-1 and BMP-2 on Ectopic and Orthotopic Bone Formation

Abstract: PurposesThe potent stem cell homing factor stromal cell-derived factor-1 (SDF-1) actively recruits mesenchymal stem cells from circulation and from local bone marrow. It is well established that bone morphogenetic protein-2 (BMP-2) induces ectopic and orthotopic bone formation. However, the exact synergistic effects of BMP-2 and SDF-1 in ectopic and orthotopic bone regeneration models have not been fully investigated. The purpose of this study was to evaluate the potential effects of simultaneous SDF-1 and BMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 38 publications
(51 reference statements)
0
19
1
Order By: Relevance
“…In contrast, a recent study by Lee et al found no synergistic effect of BMP‐2 and SDF‐1α on bone regeneration using a critical size murine calvarial bone defect and collagen sponges as scaffolds . The authors used SDF‐1α doses between 0.1 and 1 µg, which is 10 to 100 times lower than the dose we used in the current study.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…In contrast, a recent study by Lee et al found no synergistic effect of BMP‐2 and SDF‐1α on bone regeneration using a critical size murine calvarial bone defect and collagen sponges as scaffolds . The authors used SDF‐1α doses between 0.1 and 1 µg, which is 10 to 100 times lower than the dose we used in the current study.…”
Section: Discussioncontrasting
confidence: 69%
“…using a critical size murine calvarial bone defect and collagen sponges as scaffolds. 24 The authors used SDF-1a doses between 0.1 and 1 mg, which is 10 to 100 times lower than the dose we used in the current study. This might be an explanation for the missing cumulative effect.…”
Section: Discussionmentioning
confidence: 90%
“…The dose we chose (1 μg of BMP2) should cause bone formation in vivo. 26 , 27 , 28 , 29 , 30 , 31 To further understand the mechanism causing no bone formation in this group, we performed a BMP2 release experiment from PLLA. We loaded 1 μg of BMP2 into a scaffold, incubated it in PBS, and collected the solution at a different time point.…”
Section: Discussionmentioning
confidence: 99%
“…To further explore if RUNX2 is directly related to Rg1-induced angiogenesis, we performed a tube formation assay. This system mimics the reorganization of endothelial cells into a three-dimensional network during angiogenesis [ 28 , 29 ]. Since the number of branch points reflects angiogenic activity in endothelial cells, we observed the capillary structures of HUVECs under various treatments.…”
Section: Resultsmentioning
confidence: 99%